2018
DOI: 10.1021/acsami.8b07030
|View full text |Cite
|
Sign up to set email alerts
|

Heterostructure WSe2−Ga2O3 Junction Field-Effect Transistor for Low-Dimensional High-Power Electronics

Abstract: Layered materials separated from each bulk crystal can be assembled to form a strain-free heterostructure by using the van der Waals interaction. We demonstrated a heterostructure n-channel depletion-mode β-GaO junction field-effect transistor (JFET) through van der Waals bonding with an exfoliated p-WSe flake. Typical diode characteristics with a high rectifying ratio of ∼10 were observed in a p-WSe/n-GaO heterostructure diode, where WSe and β-GaO were obtained by mechanically exfoliating each crystal. Layere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 40 publications
2
84
0
Order By: Relevance
“…[12] Recent studies of 2D materials [13] have revealed a variety of 2D semiconductors (2DSCs) with excellent electronic properties [14][15][16][17] and ultrathin body thickness. However, despite several studies on 2DSCs based JFETs reported to date, [23][24][25][26] the SS achieved in these devices remain > 100 mV dec −1 , far from the ideal value of 60 mV dec −1 . [11] Additionally, the dangling bond free van der Waals (vdW) interface formed by 2DSCs could feature a trapping free interface to promise nearly ideal junction characteristics.…”
Section: Doi: 101002/adma201902962mentioning
confidence: 91%
See 4 more Smart Citations
“…[12] Recent studies of 2D materials [13] have revealed a variety of 2D semiconductors (2DSCs) with excellent electronic properties [14][15][16][17] and ultrathin body thickness. However, despite several studies on 2DSCs based JFETs reported to date, [23][24][25][26] the SS achieved in these devices remain > 100 mV dec −1 , far from the ideal value of 60 mV dec −1 . [11] Additionally, the dangling bond free van der Waals (vdW) interface formed by 2DSCs could feature a trapping free interface to promise nearly ideal junction characteristics.…”
Section: Doi: 101002/adma201902962mentioning
confidence: 91%
“…The maximum channel mobility of a JFET can be calculated by expression [23,24] We also investigated the output characteristics (Figure 2d) of the SnSe/MoS 2 JFET at various top-gate voltage. The maximum channel mobility of a JFET can be calculated by expression [23,24] We also investigated the output characteristics (Figure 2d) of the SnSe/MoS 2 JFET at various top-gate voltage.…”
Section: Doi: 101002/adma201902962mentioning
confidence: 99%
See 3 more Smart Citations